معاملة المجتمع المسلم الاندونيسي من قبل القرآن والحديث - Abdul Hakim Wahid (Al-Zahra : Journal for Islamic and Arabic Studies, 2022)
This article aims to learn how Indonesian Muslims treat the Quran and Hadith in their daily lives, and in particular to uncover the secrets of using Surat al-Duha as a means of searching for the missing things. This article was written based on the results of induction using the qualitative and descriptive approach with main sources are the results of interviews with the educator and students of the Islamic Kindergarten Institute, with other sources related to this research. This article concluded that the reason for using Surat al-Duha as a tool to search for something missing has to do with the interpretation of Surat al-Duha reinforced by the Hadith of the Prophet. And The word "lost" considered in the seventh verse which has the meaning of perplexity as a word that contains the power to help man to find the thing that is missing. Although the hadith of the Prophet which confirms the virtue of reading this surah is incorrect, it is even the content in it is proven after its practice.  Therefore, this article concludes that many Indonesian society use the Qur'an as a reading to reach their life goals, and uses the Hadith of the Prophet without regard to its authenticity.